Evaluation of Biological Water Quality by Biological Macrophytic Index in River: Application on the Watershed of Beht River - Saloua, Bentaibi; Abdelilah, Rahou; Lahsen, Chillasse; Soumaya, Hammada; Elhassan, Abba (European Scientific Journal, ESJ, 2017)
The Biological macrophytic Index for River (IBMR) is based on the examination of aquatic plants (macrophytes) to determine the river quality, particularly its degree of eutrophication linked to nitrogen content and phosphorus in water . The aim of this study was to evaluate the biological quality of a Moroccan river through the IBMR in view to integrate it into the monitoring programs of water quality. Indeed, this method of assessment of biological water quality is under development and adaptation to the Moroccan hydro-biological context. Beht River on which we selected 13 stations, the quality was evaluated during a first sampling campaign in 2014. The results show a good representation of the trophic status of stations relative to environmental conditions of the environment such as the types of wastes, agricultural and other activities. Indeed, the stations with a strong trophic level often come downstream urban areas or near farms. The low average index values correspond to stations with little to very little polluting activities.